All the devils - Eisler, Barry (Thomas & Mercer, 2019)
Ten years ago, the daughter of Homeland Security Investigations agent B. D. Little vanished into thin air. So did seven other girls<U+2014>the crimes all bearing the same signature characteristics. Now the disappearances have begun again. And Agent Little<U+2019>s efforts to investigate are being blocked by forces far above his pay grade. Desperate, he turns to Seattle sex-crimes detective Livia Lone, the most obsessive hunter of predators Little knows. Livia will need that obsessiveness, and a lot more. Because the two men Little is pursuing are fearsome. Both Special Forces veterans with a dozen tours in Iraq between them. Both sadists and serial rapists. And one, the congressman scion of the vice president of the United States<U+2014>a man who will use all his power to protect his son<U+2019>s secrets and further his own ambitions. The conspirators have all the assets and all the angles. And every reason to believe they<U+2019>ll evade justice, as they always have before. They don<U+2019>t understand that for Livia Lone, justice is only a guideline. Revenge is the rule.